Consumer engagement behaviors in the online wildlife trade: Implications for conservationists. Issue 12 (17th December 2020) - Feddema, Kim; Harrigan, Paul; Nekaris, K. Anne Isola; Maghrifani, Dila
Abstract: This study investigates consumer engagement behaviors in the online wildlife trade, drawing implications for conservationists. The first study undertook a quantitative content analysis of 500 Facebook posts in wildlife trade lateral exchange markets to show how creative strategies, media type and persuasion tactics influence the number of likes and comments that posts receive. The second study then undertook a thematic discourse analysis to develop a rich understanding of the culture, beliefs and motivations that influence how consumers engage in the markets. Findings showed that an overwhelming majority of posts use a functional or informational strategy and that when posts use overt persuasion tactics the number of comments decrease. A conceptual model of how cultural factors may impact the success of marketing strategies is then proposed. These findings have implications for conservationists who seek to build engagement with wildlife trade consumers online.